How do health professionals decide whether an interpreter is needed for families in neonatal and pediatric units?. Issue 9 (September 2019) - Jones, Liz; Sheeran, Nicola; Pines, Rachyl; Saunders, Bradley
Highlights: Health professionals findit difficult to decide whether an interpreter is needed. Health professionals' attitudes and goals affect their decision making about interpreters. There is marked variability in the decision-making processindividual health professionals use. Training is needed, including a decision tool, to assist health professionals' decisions. Abstract: Objective: To examine how health professionals decide whether family members require an interpreter. Methods: 69 health professionals, doctors, nurses, and allied health, from neonatal and pediatric units participated. Interviews used a verbal protocol analysis, which elicited their thoughts about using interpreters, including how they decided if an interpreter was needed. Results: Five themes captured the decision-making process health professionals use. Of these, three themes described the goals and beliefs participants brought to their interactions with family members: Ensuring understanding, Addressing socioemotional needs, and Who decides. The theme Assessing understanding was prominent within the interaction, while the final theme was Contextual factors influencing decision making. No differences were found between mono and multilingual participants, and few differences between health professional groups. Conclusion: Health professionals find it difficult to assess whether a family member needs an interpreter and there is no consistency in how they make this decision, with some using heuristics and others a more systematic approach. Health professionals have beliefs about the purpose of an interpreter that potentially limit the voice of family members. Practice implications: Health professionals need training to assist them in decisions about whether an interpreter is needed, including a decision tool and knowledge about policies.